Analisis Model Budaya Tandingan Menurut Ulangan 22 :13-30 Serta Kaitanya Dengan Hukum Perkawinan Dalam Masyarakat Toraja - Mariana Banne (Sekolah Tinggi Teologi Simpson Ungaran, 2023)
The existence of this journal is made which discusses the views of the Toraja people about Rampanan Kapa' or commonly referred to as marriage, but to find out the law of Rampanan kapa', the author in making this journal will discuss how the public views the law of Rampanan kapa', why it happens in marriages in Toraja and what is done by the Toraja people to achieve Rampnana kapa' as stipulated in the Law About Marriage No. 1 of 1974. The purpose and usefulness of this journal are to provide every reader with knowledge about marriage law and its implementation forms in Torajan society. Both to the general public and to the Torajan people so that marriage is carried out for the purposes regulated by law without ignoring the value of customs that apply in Toraja and have become a habit by the Torajan people. But in this case, also the marriage of the Toraja people is associated with a counterculture model that supports the existence of customs that are obeyed by each community in their respective regions so that by understanding this counterculture, we increasingly understand the law in conducting marriage or Rampanan kapa' in Torajan society. In Torajan society, there are customs as the identity of Torajan people that can be introduced to anyone while still respecting the existence of other people's culture. Our culture as Torajan people can be introduced wherever we are by practicing our culture in the country of people but still respecting the culture in the area.